Determinasi Penerimaan Opini Audit Going Concern (Studi Empiris Pada Perusahaan Pertambangan yang Terdaftar di BEI Tahun 2019-2021) - Yolanda Wahyu Fitriandini; Ruci Arizanda Rahayu (-, 2023)
This study aims to analyze the effect of profitability, leverage, audit lag, company size, and company growth on acceptance of going concern audit opinions in mining sector companies listed on the IDX in 2019-2021. The selection of the sample in this study uses the purposive sampling method with the following criteria: mining companies listed on the IDX during the 2019-2021 period, companies that issue financial reports and can be accessed during the 2019-2021 period, and companies that present independent auditor reports during the 2019-2021 period . As a result, data were obtained for 23 companies that met these criteria. So if multiplied by 3 years, we can get 69 data. The research method used is a quantitative approach using logistic regression analysis. The results of this study are that profitability and company size have a negative effect on going concern audit opinions in mining companies listed on the IDX in 2019-2021. Leverage has a positive effect on going concern audit opinion of mining companies listed on the IDX in 2019-2021. Audit lag and company growth have no effect on going concern audit opinions for mining companies listed on the IDX in 2019-2021.